Estimating the impact of PSTN migration: The case of eastern Japan - Tatsuya Kurosaka; Koji Osamura; Rie Asaji; Teppei Koguchi; Masahiko Shoji; Toshiya Jitsuzumi (International Telecommunications Society (ITS), 2017)
In this research, we estimated the number of possible subscribers of the public switched telephone network (hereafter, referred to as “PSTN”) in the future of Japan based on the public data, and evaluated the alternatives as the candidates for the migration by comparative analysis, with respect to the definition of PSTN from the regulations in Japan. As the result of this analysis, the number of those subscribers in Japan will decrease to around 7.1 million households in 2030. Despite the telecommunication operators' effort to provide their own NGN, 6.8 million subscribers will remain using PSTN. Then, 0.3 million households of them are going to live in the area where the telecommunication operators will not expand their own optical fiber network if the designation of the universal service on telecommunication service will not be reformed. The result also revealed the difficulties of migration from PSTN because the regulation for PSTN did not justify many of the alternatives including Metal IP Phone, IP phone using optical fiber, CATV, MVNO using LTE.
Keywords: 330; PSTN migration; universal service; IP telephone; Telecommunications regulation; broadband